2022
DOI: 10.1124/pharmrev.121.000564
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Signaling: Examining Its Engagement with Various Molecular Targets in the Context of Binding Affinity, Concentration, and Biologic Response

Abstract: Carbon monoxide (CO) has been firmly established as an endogenous signaling molecule with a variety of pathophysiological and pharmacological functions, including immunomodulation, organ protection, and circadian clock regulation, among many others. In terms of its molecular mechanism(s) of action, CO is known to bind to a large number of hemoproteins with at least 25 identified targets, including hemoglobin, myoglobin, neuroglobin, cytochrome c oxidase, cytochrome P450, soluble guanylyl cyclase, myeloperoxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 423 publications
(512 reference statements)
0
35
0
Order By: Relevance
“…Gaseous signaling molecules refer to gaseous molecules that are synthesized within organs, tissues, or cells, or received from the environment, and are utilized to transmit chemical signals. 3 These molecules are capable of inducing particular physiological or biochemical changes, and encompass, but are not restricted to, oxygen, 4 carbon dioxide, 5 nitric oxide, 6 carbon monoxide, 7 hydrogen sulfide, 8 sulfur dioxide, 9 hydrogen cyanide, 10 ammonia, 11 and hydrogen. 12 Not all gaseous signaling molecules can be classified as gasotransmitter molecules; they need to fulfill the following prerequisites: (1) the capacity to diffuse freely through membranes, thereby making their biological effects independent of membrane receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Gaseous signaling molecules refer to gaseous molecules that are synthesized within organs, tissues, or cells, or received from the environment, and are utilized to transmit chemical signals. 3 These molecules are capable of inducing particular physiological or biochemical changes, and encompass, but are not restricted to, oxygen, 4 carbon dioxide, 5 nitric oxide, 6 carbon monoxide, 7 hydrogen sulfide, 8 sulfur dioxide, 9 hydrogen cyanide, 10 ammonia, 11 and hydrogen. 12 Not all gaseous signaling molecules can be classified as gasotransmitter molecules; they need to fulfill the following prerequisites: (1) the capacity to diffuse freely through membranes, thereby making their biological effects independent of membrane receptors.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Ample studies indicate that CO is more than just a metabolic waste, and it is highly involved in the modulation of signaling pathways in mammals. [3][4][5][6][7][8][9] For example, CO was reported to reversibly bind to core transcriptional factors, NPAS2 and CLOCK in the transcription-translation feedback loops to regulate circadian rhythms, and the selective removal of endogenous CO significantly disrupts rhythmic expression of the clock genes. [7] In addition to its physiological roles, ample studies have demonstrated that CO also plays indispensable roles under pathological conditions, and the delivery of exogenous CO conveyed a wide range of pharmacological effects both in vitro and in vivo, including anti-tumor, [10][11] anti-inflammatory, [12][13] antimicrobial, [14][15] and cytoprotective effects, [16][17][18][19] among others.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, CO is also generated endogenously at a rate of 16 μmol/hour in humans via the catabolism of heme in the presence of heme oxygenase (HO‐1/2) [2] . Ample studies indicate that CO is more than just a metabolic waste, and it is highly involved in the modulation of signaling pathways in mammals [3–9] . For example, CO was reported to reversibly bind to core transcriptional factors, NPAS2 and CLOCK in the transcription‐translation feedback loops to regulate circadian rhythms, and the selective removal of endogenous CO significantly disrupts rhythmic expression of the clock genes [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon monoxide (CO) is well-known as a “silent killer” among the general population due to its lethal toxicity at high concentrations. However, the past two decades have witnessed intensive studies in revealing the physiological roles, therapeutic activities, mechanism(s) of action, and innovative delivery approaches of CO. The prospect of developing CO into a therapeutic agent for treating various diseases is on the horizon . Compared to conventional small-molecule drugs, delivering such a gaseous molecule for therapeutic use poses unique challenges.…”
mentioning
confidence: 99%